After Decolonization, After Civil Rights: Chinua Achebe and James Baldwin - Bill Schwarz (James Baldwin Review, 2015)
The escalation of systematic, if random, violence in the contemporary world frames the concerns of the article, which seeks to read Baldwin for the present. It works by a measure of indirection, arriving at Baldwin after a detour which introduces Chinua Achebe. The Baldwin–Achebe relationship is familiar fare. However, here I explore not the shared congruence between their first novels, but rather focus on their later works, in which the reflexes of terror lie close to the surface. I use Achebe’s final novel, Anthills of the Savanah, as a way into Baldwin’s “difficult” last book, The Evidence of Things Not Seen, suggesting that both these works can speak directly to our own historical present. Both Baldwin and Achebe, I argue, chose to assume the role of witness to the evolving manifestations of catastrophe, which they came to believe enveloped the final years of their lives. In order to seek redemption they each determined to craft a prose—the product of a very particular historical conjuncture—which could bring out into the open the prevailing undercurrents of violence and terror.